General Medical Practitioners Acting as Geneticists, a Risky Business? - Dauge, Aurélie; Joly, Yann; Kaiser, Beatrice; Chiquette, Jocelyne; Lapointe, Julie; Simard, Jacques; Dorval, Michal; Nabi, Hermann (Lex Electronica, 2023)
The availability of precision medicine tools and approaches has increased considerably over the past decades, propelled by rapid scientific advances in genomics and the popularity of direct-to-consumer genetic testing. Genetic specialists working within public healthcare systems are struggling to meet the growing demand for clinical genetic services. Some experts have suggested that doctors who are not specialized in genetics could take on some of the tasks performed by genetic specialists since they are regularly the first point of contact for people with a genetic predisposition to cancer. However, expanding doctors’ roles may heighten their standard of practice and concomitant medical liability risk to that of genetic specialists. This paper reviews the medical liability regime applicable to this situation through the lens of Canada’s unique bijural legal system. We then compare the state of the law in Canada to that of the United States. According to our findings, unless there is an improvement in the quality of genetic services provided by general practitioners, we could see a growing number of successful liability suits in clinical genetics and precision medicine in the coming years. To prevent this unsatisfactory outcome, additional professional training in core genetic tasks should be made increasingly available to general practitioners and the creation of communities of practice in genetics encouraged. Furthermore, courses introducing medical students to genetics, including its ethical and legal challenges, should be made available and actively promoted within medical curricula.